2021
DOI: 10.1136/rmdopen-2021-001687
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations and outcome of SARS-CoV-2 infections in children and adolescents with rheumatic musculoskeletal diseases: data from the National Paediatric Rheumatology Database in Germany

Abstract: ObjectivesThis study aimed to investigate the clinical manifestations, course and outcome of SARS-CoV-2 infection among children and adolescents with rheumatic and musculoskeletal diseases (RMD). Due to their underlying disease as well due to therapeutic immunosuppression, these patients may be at risk for a severe course of COVID-19 or for a flare of the underlying disease triggered by SARS-CoV-2 infection.MethodsDemographic, clinical and treatment data from juvenile patients with RMD as well as data about SA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 23 publications
2
17
2
3
Order By: Relevance
“…48 Conversely, other authors reported a similarly favorable course, compared to healthy children, in patients undergoing immunosuppressive treatment for inflammatory bowel diseases, rheumatic diseases, and kidney diseases. [49][50][51] Table 1 summarizes the major risk factors for severe COVID-19 in pediatric patients.…”
Section: Sars-cov-2 Infection and Covid-19 In Children Andmentioning
confidence: 99%
“…48 Conversely, other authors reported a similarly favorable course, compared to healthy children, in patients undergoing immunosuppressive treatment for inflammatory bowel diseases, rheumatic diseases, and kidney diseases. [49][50][51] Table 1 summarizes the major risk factors for severe COVID-19 in pediatric patients.…”
Section: Sars-cov-2 Infection and Covid-19 In Children Andmentioning
confidence: 99%
“…In line with our findings, their results suggest that associated comorbidities and treatment with glucocorticoids increase the risk of hospital admission [ 12 ]. Results from the national paediatric rheumatology database in Germany show similar results, with 76 cases of COVID-19 in children with rheumatic diseases, with mild outcome and good recovery in the majority of cases, and no relevant impact on disease activity [ 13 ].…”
Section: Discussionmentioning
confidence: 90%
“…In a study from Germany, the clinical manifestations, course, and outcome of SARS-CoV-2 infection in 76 children with rheumatic diseases (44 with JIA) from April 2020 to February 2021 were analyzed. In 76% of patients under various immunosuppressive medications, SARS-CoV-2 infection was mild with good outcome in the majority of cases and did not have a relevant impact on rheumatic disease activity [ 10 ].…”
Section: Discussionmentioning
confidence: 99%